Response of the bacterioplankton composition to inorganic nutrient loading and phytoplankton in southern Korean coastal waters: A mesocosm study. (23rd April 2020) - Park, Bum Soo; Lee, Minji; Shin, Kyoungsoon; Baek, Seung Ho
Abstract: In Korean coastal waters (KCW), nutrient loading from the four major rivers usually peaks in summer, probably due to the large amount of water discharge in rainy seasons, but little is known about the responses of the bacterial community composition to inorganic nutrient loading. To gain deeper understanding of variations in marine microbial biodiversity and function with inorganic nutrient loading, a large‐scale mesocosm (1, 000 L) experiment was conducted in southern KCW for 10 days in summer (July 27 through August 6, 2015) and the bacterioplankton community composition (BCC) was investigated using 16S rRNA amplicon pyrosequencing method. The bioassays established in the mesocosm were designed with the following each nutrient dosing treatments: nitrate (+N), phosphate (+P), and nitrate plus phosphate (+NP). Among the three treatments, the +NP and +N treatments exhibited the largest and second‐largest increases in phytoplankton abundance, respectively, whereas there was relatively less variation under the +P treatment. Enhanced growth of phytoplankton not only induced increases in pH and bacterial abundance ( p < .05) but also led to changes in the BCC: the orders Flavobacteria, Micrococcales, Oceanospirillales, and Rhodobacterales exhibited increases in relative abundance, whereas Methylophilales, Puniceicoccales, SAR11, SAR116, and SAR86 showed a decreasing trend. Inorganic nutrients may directly contribute to variation in the BCC, as the relative abundance of Sphingobacteriales, containing members that undergo chemotaxis toward inorganic nutrients, was increased by the +N treatment. Given that these findings, changes in phytoplankton abundance due to nutrient addition may be the most crucial component resulting in variation in the BCC.